Integrating Multiple Representations and Augmented Reality in Maritime Chemistry E-Module Based on IMO 7.04 - Suryaningsih, Encis Indah; Nafillah, Khoirotun; Aprillina, Aprillina (Universitas Negeri Medan, 2025)
Chemistry is essential for maritime engineering students, but many concepts are abstract and difficult to understand due to limited resources that integrate macroscopic, microscopic, and symbolic representations. This study aimed to develop and validate a maritime chemistry e-module that combines multiple representations with Augmented Reality (AR) technology, aligned with IMO Model Course 7.04. The research employed the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. Data were collected through expert validation sheets and student response questionnaires, and analyzed using percentage analysis. The results showed that the e-module achieved very valid criteria, with average feasibility values of 92.75% for material and 98.09% for media aspects. Student responses indicated high acceptance in terms of appearance, design, ease of use, content comprehension, interactivity, engagement, and perceived benefits, with an overall score of 87.36% classified as very good. In conclusion, the multiple representation-based AR e-module provides maritime engineering students with a practical, contextual, and engaging learning tool, enhancing conceptual understanding in maritime chemistry.